Revision as of 17:41, 7 October 2008 by Park1 (Talk)

$ x(t) = e^{-|t-1|} \, $

$ X(w) = \int_{-\infty}^{\infty}e^{-|t-1|}e^{-jwt}dt $

$ X(w) = \int_{-\infty}^{\1}e^{(t-1)}e^{-jwt}dt+\int_{1}^{\infty}e^{-(t-1)}e^{-jwt}dt $

$ X(w) = \int_{-\infty}^{\1}e^{-1}e^{(1-jw)t}dt+\int_{1}^{\infty}e^{1}e^{(1+jw)t}dt $

$ X(w) = e^{-1}\frac{e^{(1-jw)t}}{1-jw}\right]^{\infty}_0 }+e^{1}\frac{e^{-(1+jw)t}}{1+jw}\right]^{\infty}_0 } $

Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett